The Efficacy of Autologous Myoblast Sheet Transplantation to Prevent Perforation After Duodenal Endoscopic Submucosal Dissection in Porcine Model - Matsumoto, Ryo (Cell Transplant, 2020)
The recent advent of endoscopy has enabled the endoscopic submucosal dissection (ESD) of superficial nonampullary duodenal epithelial tumors. However, the substantially thin wall and presence of bile and pancreatic juice make it technically difficult to perform duodenal ESD without perforation, which leads to lethal complications. The present study evaluated the efficacy of autologous myoblast sheet transplantation for the prevention of late perforation after duodenal ESD in a porcine model. Two weeks before ESD, skeletal muscle was surgically excised from the femur of pigs, and myoblasts were isolated and seeded in temperature-responsive culture dishes to prepare sheets. Immediately after ESD, the autologous myoblast sheets were attached to the serosal surface at the ESD site with omentopexy. The pigs were divided into two groups: the autologous myoblast sheet group (n = 5), where the myoblast cell sheet was attached to the ESD ulcer part from the duodenal serous side, and the Omentum group (n = 5), where only the omentum was used. The pigs were sacrificed and analyzed macroscopically and histologically on postoperative day 3. The macroscopic examination of the abdominal cavity revealed perforation in the ESD ulcer area and leakage of bile in the Omentum group but no perforation in the Sheet group. A histopathological examination revealed that continuity of the duodenal wall at the ESD site was maintained with dense connective tissue in the Sheet group. In conclusion, autologous myoblast sheets were useful for preventing perforation after duodenal ESD.